PENERAPAN METODE PEMBELAJARAN DRILL AND PRACTICE UNTUK MENINGKATKAN KEMAMPUAN SPEAKING DAN VOCABULARY (Studi Pada Mata Pelajaran Bahasa Inggris Kelas XI) SMK Negeri 2 Lahat - Wimbika Hastenti (UNIB Press, 2020)
The research purpose is to describe the application of Drill and Practice learning methods to improve the speaking and vocabulary skills of students of class XI OTKP SMK Negeri 2 Lahat. The study design was the Classroom Action Research (CAR) model of Kemmis and Taggart, which was followed by a quasi experiment. The research subjects were students of class XI OTKP 1 even semester of the 2019/2020 school year SMK Negeri 2 Lahat. For quasi-experimental samples are class XI OTKP 1 and OTKP 3. Classroom action research totaling 25 students, for the experimental class totaling 25 students and the control class totaling 25 students. Data collection techniques in this research used a research sheet. Data analysis uses mean (percentage) percentages and t-tests. The conclusion of this research indicate that the application of the Drill And Practice method can improve students' speaking and vocabulary abilities.